The value of real world data in healthcare decision-making : practical applications using observational data from the National Hepatitis C Treatment Registry - Gray, Emma (Trinity College (Dublin, Ireland). School of Medicine. Discipline of Clinical Medicine, 2017)
Introduction: Observational research can play an integral role in the healthcare decision-making process. In an era of ever increasing drug costs, healthcare decision-makers are under pressure to optimally allocate resources. It is essential they have access to a comprehensive evidence base to inform their decisions. Since the approval of the direct-acting antiviral (DAA) agents in Ireland in 2012, the hepatitis C (HCV) treatment landscape has been transformed. This was identified as an opportune time to maximise the therapeutic management of HCV infection in Ireland. Thus, the national HCV treatment registry was established. This thesis aims to utilise the registry to generate robust real world data to assess the impact of these regimens in the post-reimbursement era, and to demonstrate the value and practical application of observational data in healthcare decision-making. Methods: The registry utilises a prospective, longitudinal, observational cohort study. The effectiveness of the DAA regimens was established following analysis of the registry data. Micro-costing studies were undertaken to establish the cost of HCV-related healthcare for patients i) receiving DAA treatment ii) following premature discontinuation and iii) following achievement of a sustained virological response (SVR). Ambulatory care costs were compared with those of an untreated cohort. The perception, knowledge and attitudes to the registry among key stakeholders were determined through an online survey. A systematic literature review identified all published literature reporting the efficacy or effectiveness of licensed regimens for genotype (GT) 1 HCV-infected patients. This facilitated the comparison of our outcomes with other studies and informed a network meta-analysis (NMA) which aimed to assess the impact of including observational data in the estimation of the relative treatment effect of agents for the treatment of GT1 infection. We applied our effectiveness and cost data to an independently produced economic model and compared the output with the original analysis when RCT data and costs from other literature sources were inputted into the model. Results: SVR rates in the Irish clinical setting were comparable with the efficacy rates reported in RCTs when matched to similar patient populations, and our data generated real world data for subpopulations of patients excluded from these pivotal clinical trials. The SVR rates in the interferon (IFN)-free regimens (87%-90%) were higher than the SVR rates from IFN-based regimens (45%-74%). The mean per-patient cost of treatment with IFN-based regimens was €38,286 vs. €55,734 in IFN-free regimens primarily reflected by the higher drug acquisition costs for IFN-free regimens. Premature discontinuation was costly (€1,947 and €870 in those with and without cirrhosis, respectively). Following achievement of a SVR, patients with advanced cirrhosis continued to incur significant ambulatory costs attributable to the requirement for continued screening and higher risk of admission. The addition of observational data to the NMA did not have an impact on the relative treatment effect, potentially attributable to methodological issues. In the economic model, input parameters incorporating real world data had a significant impact on the cost-effectiveness of treatment regimens. The majority of key stakeholders (79%) were satisfied with their involvement in the HCV treatment registry, and the on-going monitoring of clinical and cost outcomes had practical implications in the management of patient undergoing treatment for HCV infection. Conclusion: The generation and subsequent practical application of observational data derived from a treatment registry has demonstrated the value of such data for decision-makers in the Irish setting. It has had a direct impact on health policy in Ireland through its integral role in the establishment of the National Hepatitis C Clinical Programme and the on-going generation of robust real world data will be highly valuable to healthcare policy-makers, when incorporated with all other available evidence, as they continue to manage the budget impact of HCV infection in Ireland. This study indicates the feasibility of applying the methods and findings from this work to other high-cost therapeutic areas in Ireland.
Keywords: Clinical Medicine, Ph.D.; Ph.D. Trinity College Dublin